The House of Death : Messages from the English Renaissance - STEIN, ARNOLD (Book collections on Project MUSE., 2020)
In The House of Death, Arnold Stein studies the ways in which English poets of the sixteenth and seventeenth centuries imagined their own ends and wrote of the deaths of those they loved or wished to honor. Drawing on a wide range of texts in both poetry and prose, Stein examines the representations, images, and figurative meanings of death from antiquity to the Renaissance. A major premise of the book is that commonplaces, conventions, and the established rules for thinking about death did not prevent writers from discovering the distinctive in it. Eloquent readings of Raleigh, Donne, Herbert, and others capture the poets approaching their own death or confronting the death of others. Marvell's lines on the execution of Charles are paired with his treatment of the dead body of Cromwell; Henry King and John Donne both write of their late wives; Ben Jonson mourns the death of a first son and a first daughter. For purposes of comparison, the governing perspective of the final chapter is modern.